Mm (Mo3S11) n / Ni Foam catalyst with nano-network structure as well as preparation method and application of Mm (Mo3S11) n / Ni Foam catalyst
By using Mm(Mo3S11)n/Ni Foam catalyst in the PMS activation advanced oxidation process, the problem of limited active radicals in the prior art is solved, and efficient degradation of difficult-to-degrade organic pollutants is achieved.
Patent Information
- Application Number
- CN202510057305.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-08
AI Technical Summary
Prior art In the advanced oxidation process activated by peroxy monosulfate (PMS), spontaneously generated active free radicals are limited, limiting the efficient degradation of difficult-to-degrade organic pollutants.
By adding metal salt ions M2+ to the colloidal solution of (NH4)2Mo3S13·2H2O, the self-assembly of [Mo3S13]2-cluster and M2+ ions is promoted by electrostatic action to form Mm(Mo3S11)n ultra-small nanosheets, and adding them to the foam nickel substrate to prepare an Mm(Mo3S11)n/Ni Foam catalyst with a nanonetwork structure.
This catalyst forms the maximum active site by exposing more unsaturated S ligands, reducing the adsorption activation energy on PMS, significantly improving the activity of the catalyst, and effectively removing organic pollutants such as tetracycline hydrochloride in a short period of time.
Smart Images

Figure CN119771449A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a catalyst having a nano-network structure. m (Mo3S 11 ) n / Ni Foam catalyst and its preparation method and application. Background Art
[0002] The abuse of antibiotics poses an increasingly serious threat to the ecosystem. Among the existing pollutant degradation technologies, the advanced oxidation process based on peroxymonosulfate (PMS) activation has been widely used to remove difficult-to-degrade organic pollutants due to its unique advantages. The above process introduces light-assisted activation of PMS to produce more active species and improve the degradation efficiency of organic pollutants. However, the spontaneously generated active free radicals are very limited, which limits the large-scale application of this technology. Therefore, it is particularly important to explore efficient catalysts for advanced oxidation processes based on PMS activation.
[0003] MoS2 has been widely studied in the field of PMS activation due to its typical two-dimensional layered structure. However, because its basal surface is inert, its catalytic active sites are very limited. Studies have shown that the edge active sites of MoS2 can be effectively increased by increasing the surface area of the material through substrate dispersion. Among them, nickel foam (Ni Foam) is regarded as an ideal substrate for loading powder materials due to its three-dimensional porous structure. In addition, the intrinsic activity of MoS2-based materials can be greatly improved by adjusting the coordination environment of the Mo-S bond. The Chinese patent with application number CN202210517687.0 discloses a method for preparing a MoS2 / nickel foam composite electrode material, but it mainly increases the specific surface area of the material through a sea urchin-like morphology, which is very limited for improving the intrinsic activity of the MoS2 material.
[0004] Compared with crystalline MoS2, [Mo3S 13 ] 2- Cluster-constructed amorphous MoS x is another type of sulfur-rich catalyst. Structurally, a triangular framework of [Mo3S 13 ] 2- The cluster contains a central apical sulfur (api-S 2- ), three bridging sulfur (bri-S2 2- ) and three terminal sulfur (ter-S2 2- ). When two bri-S2 2- The ligands are randomly linked together to form polymer chains (Mo3S 11 ) n When the sulfur atoms are ions, they can be regarded as edge active sites. The latest research shows that amorphous MoS xThe electrocatalytic activity for hydrogen evolution reaction is highly efficient. At the same time, it also performs well as a highly reversible cathode material for magnesium ion batteries. These results show that [Mo3S 13 ] 2- The unique molecular structure of the cluster significantly improves the catalytic efficiency. Therefore, it is necessary to develop and design (Mo3S 11 ) n Based on this, the present invention proposes a simple, convenient and large-scale preparation method of M m (Mo3S 11 ) n / Preparation method of Ni Foam catalyst. Summary of the invention
[0005] The first object of the present invention is to provide a nano-network structure. m (Mo3S 11 ) n / The preparation method of Ni Foam catalyst is simple and easy to operate.
[0006] The second object of the present invention is to provide a nano-network structure. m (Mo3S 11 ) n / Ni Foam catalyst has excellent ability to remove organic pollutants.
[0007] The third object of the present invention is to provide a nano-network structure. m (Mo3S 11 ) n / The application of Ni Foam catalyst has broad application prospects.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] A M with a nano-network structure m (Mo3S 11 ) n The preparation method of the Ni Foam catalyst comprises the following steps:
[0010] (1) To (NH4)2Mo3S 13 After adding metal salt M to the 2H2O colloidal solution, M is obtained through self-assembly m (Mo3S 11 ) n Solution;
[0011] (2) Replace the M in step (1) m (Mo3S 11 ) nThe solution is added to the cleaned nickel foam substrate and self-assembled to obtain the product.
[0012] Furthermore, the metal salt M, (NH4)2Mo3S 13 The mass ratio of 2H2O is 1:(3-10); the metal salt M is selected from one of nickel salt, cobalt salt, copper salt and ferrous salt; the self-assembly time is 12-24h.
[0013] By adding (NH4)2Mo3S 13 ·Introducing metal ions M into the 2H2O colloidal solution 2+ , using electrostatic interaction to promote [Mo3S 13 ] 2- Clusters and M 2+ The self-assembly process of ions forms M m (Mo3S 11 ) n Ultra-small nanosheets. In addition, [Mo3S 13 ] 2- Clusters and M 2+ Ion coordination can further reduce M m (Mo3S 11 ) n Adsorption activation energy on PMS.
[0014] Precise metal salt M and (NH4)2Mo3S 13 The mass ratio of 2H2O helps control the reaction path, thereby improving the selectivity of the target product and reducing the formation of by-products.
[0015] Controlling the self-assembly time to 12-24h can make the polymerization reaction more complete and is beneficial to M m (Mo3S 11 ) n growth and formation.
[0016] Furthermore, the nickel salt is nickel nitrate, the cobalt salt is cobalt nitrate, the copper salt is copper nitrate, and the iron salt is ferrous nitrate.
[0017] Furthermore, in step (1), the (NH4)2Mo3S 13 The concentration of 2H2O colloidal solution is 1-4 mg / mL.
[0018] Furthermore, in step (1), the (NH4)2Mo3S 13 ·2H2O colloidal solution is composed of (NH4)2Mo3S 13 ·2H2O dissolved in DMF, (NH4)2Mo3S 13The preferred ratio of 2H2O to DMF is 1 mg:0.3 mL. The exact solute ratio can ensure the maximum solubility of the solute in the solvent, avoid supersaturation and precipitation, and cause the solution to exhibit the Tyndall effect.
[0019] Further, in step (2), M m (Mo3S 11 ) n The dosage of the solution is 0.1-0.4mL / cm 2 ; The value range of m is 0.0028-0.0176, and the value range of n is 0.0064-0.0128.
[0020] M m (Mo3S 11 ) n Too much solution can easily increase the interaction forces such as van der Waals force, thus causing agglomeration. However, too little solution can fail to achieve the expected assembly effect, thus affecting its function.
[0021] Furthermore, in step (2), M m (Mo3S 11 ) n The solution was added to the cleaned nickel foam substrate at a drop casting rate of 0.2-0.8 mL / min.
[0022] Furthermore, the self-assembly temperature in step (2) is 40-60° C., and the self-assembly time is 3-5 h.
[0023] Furthermore, the cleaning process in step (2) is to use 1 mol / L hydrochloric acid and anhydrous ethanol for ultrasonic cleaning for 12 minutes.
[0024] Furthermore, in step (1), the (NH4)2Mo3S 13 The preparation process of 2H2O is as follows: sulfur powder is added to ammonium sulfide solution to obtain polyammonium sulfide solution; ammonium molybdate is added to the polyammonium sulfide solution for reaction, and the obtained product is obtained after purification.
[0025] Furthermore, the usage ratio of the ammonium sulfide solution to the sulfur powder is (3-4) mL: 1 g; the usage ratio of the ammonium polysulfide solution to ammonium molybdate is (30-60) mL: 1 g; and the concentration of the ammonium polysulfide solution is 20-25%.
[0026] Furthermore, the reaction temperature is 90-95° C., and the reaction time is 4-5 days.
[0027] A M with a nano-network structure m (Mo3S 11 ) n / Ni Foam catalyst is prepared by the above preparation method.
[0028] The above-mentioned M having a nano-network structure m (Mo3S 11 ) n Application of / Ni Foam catalyst in activated PMS oxidative degradation of organic pollutants.
[0029] Furthermore, the organic pollutant is tetracycline hydrochloride.
[0030] The beneficial technical effects of the present invention are:
[0031] (1) The preparation method of the present invention is to prepare a metal salt ion M 2+ and [Mo3S 13 ] 2- The clusters are randomly linked to form M with ultra-small nanosheet structures. m (Mo3S 11 ) n solution, and then M m (Mo3S 11 ) n The solution was added to nickel foam to obtain MoS x / Foamed nickel catalyst. Among them, the metal salt ion M 2+ and [Mo3S 13 ] 2- The disordered linkage of clusters will expose more unsaturated S ligands, thus forming the largest active site; and the metal salt ion M 2+ and [Mo3S 13 ] 2- The coordination of the clusters further reduces the M m (Mo3S 11 ) n The adsorption energy barrier on PMS is reduced, thereby improving the activity of the catalyst and efficiently removing tetracycline hydrochloride in a shorter time.
[0032] (2) M provided by the present invention m (Mo3S 11 ) n / Ni Foam catalyst preparation method is simple, low cost, conducive to large-scale preparation. In addition, the preparation method also solves the problem of M m (Mo3S 11 ) n The powder is difficult to collect and easily dissolves in water, causing secondary pollution.
[0033] (3) M prepared by the present invention m (Mo3S 11 ) n / Ni Foam catalyst is more conducive to recycling and reuse, and can better activate PMS and degrade organic pollutants regardless of light or dark conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The Ni obtained in Example 1 0.0068 (Mo3S 11 ) 0.0128 / SEM image of Ni foam catalyst;
[0035] Figure 2 The Ni obtained in Example 1 0.0068 (Mo3S 11 ) 0.0128 / XRD pattern of Ni foam catalyst;
[0036] Figure 3 The Ni obtained in Example 1 0.0068 (Mo3S 11 ) 0.0128 / Ni foam catalyst and control group Ni foam in the persulfate advanced oxidation system to degrade tetracycline hydrochloride effect diagram;
[0037] Figure 4 Ni obtained in Example 1 under different illumination conditions 0.0068 (Mo3S 11 ) 0.0128 / The effect of Ni foam catalyst in the degradation of tetracycline hydrochloride in persulfate advanced oxidation system;
[0038] Figure 5 M obtained in Example 1-4 m (Mo3S 11 ) n / The effect of Ni Foam catalyst in the degradation of tetracycline hydrochloride in the persulfate advanced oxidation system;
[0039] Figure 6 This is a diagram showing the effect of the materials obtained in Comparative Examples 1-5 on the degradation of tetracycline hydrochloride in a persulfate advanced oxidation system. DETAILED DESCRIPTION
[0040] The following is a further detailed description of the present invention in conjunction with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For those of ordinary skill in the technical field to which the present invention belongs, without departing from the concept of the present invention, several simple deductions or replacements can also be made, all of which should be deemed to belong to the protection scope of the present invention. The specific conditions not indicated in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.
[0041] Example
[0042] Example 1
[0043] This embodiment provides a nano-network structure. m (Mo3S 11 ) n / Ni Foam catalyst preparation method, the specific steps are as follows:
[0044] 40g of sulfur powder was added to 120mL of ammonium sulfide solution to obtain a polysulfide ammonium solution with a concentration of 25%; 4g of ammonium molybdate was then added to 120mL of the polysulfide ammonium solution, and the mixture was reacted in an oil bath at 95°C for 5 days to obtain a crude product, which was then washed with 400mL of carbon disulfide and deionized water, centrifuged at 6000r / min, and dried at 60°C for 10h to obtain (NH4)2Mo3S 13 ·2H2O; 10mg(NH4)2Mo3S 13 2H2O was dissolved in 3mL DMF to obtain (NH4)2Mo3S 13 ·2H2O colloidal solution, to (NH4)2Mo3S 13 ·2H2O colloidal solution was added with 2mg Ni(NO3)2·6H2O, and after standing for 24h, the Ni self-assembled based on electrostatic attraction was obtained. 0.0068 (Mo3S 11 ) 0.0128 Solution, 7mL of Ni 0.0068 (Mo3S 11 ) 0.0128 The solution was dripped at a rate of 0.2 mL / min onto a nickel foam substrate (5 cm × 5 cm) that had been ultrasonically cleaned with 1 mol / L hydrochloric acid and anhydrous ethanol for 12 min, and self-assembled at 60 °C for 4 h to obtain a M with a nano-network structure. m (Mo3S 11 ) n / Ni Foam catalyst, named Ni 0.0068 (Mo3S 11 ) 0.0128 / Nifoam catalyst.
[0045] This embodiment also provides a nano-network structure M m (Mo3S 11 ) n / Ni Foam catalyst is prepared by the above preparation method.
[0046] Example 2
[0047] This embodiment provides a nano-network structure.m (Mo3S 11 ) n The preparation method of / Ni Foam catalyst comprises the following specific steps: adding 30g sulfur powder to 120mL ammonium sulfide solution to obtain a polysulfide ammonium solution with a concentration of 20%; then adding 3g ammonium molybdate to 120mL of the polysulfide ammonium solution, reacting in an oil bath at 90°C for 4d to obtain a crude product, then washing with 400mL carbon disulfide and deionized water, centrifuging at 6000r / min, and drying at 60°C for 10h to obtain (NH4)2Mo3S 13 ·2H2O; 10mg(NH4)2Mo3S 13 2H2O was dissolved in 3mL DMF to obtain (NH4)2Mo3S 13 ·2H2O colloidal solution, to (NH4)2Mo3S 13 ·1 mg Cu(NO3)2 was added to the 2H2O colloidal solution and allowed to stand for 12 h to obtain the Cu self-assembled by electrostatic attraction. 0.0053 (Mo3S 11 ) 0.0128 Solution, 3mL Cu 0.0053 (Mo3S 11 ) 0.0128 The solution was dripped at a rate of 0.2 mL / min onto a nickel foam substrate (5 cm × 5 cm) that had been ultrasonically cleaned with 1 mol / L hydrochloric acid and anhydrous ethanol for 12 min, and self-assembled at 40 °C for 4 h to obtain a M with a nano-network structure. m (Mo3S 11 ) n / Ni Foam catalyst, named Cu 0.0053 (Mo3S 11 ) 0.0128 / Nifoam catalyst.
[0048] This embodiment also provides a nano-network structure M m (Mo3S 11 ) n / Ni Foam catalyst is prepared by the above preparation method.
[0049] Example 3
[0050] This embodiment provides a nano-network structure. m (Mo3S 11 ) n / Ni Foam catalyst preparation method, the specific steps are as follows:
[0051] 30g of sulfur powder was added to 100mL of ammonium sulfide solution to obtain a polysulfide ammonium solution with a concentration of 23%; 2g of ammonium molybdate was then added to 100mL of the polysulfide ammonium solution, and the mixture was reacted in an oil bath at 90°C for 4 days to obtain a crude product, which was then washed with 400mL of carbon disulfide and deionized water, centrifuged at 6000r / min, and dried at 60°C for 10h to obtain (NH4)2Mo3S 13 ·2H2O; 5mg(NH4)2Mo3S 13 2H2O was dissolved in 3mL DMF to obtain (NH4)2Mo3S 13 ·2H2O colloidal solution, to (NH4)2Mo3S 13 ·2H2O colloidal solution was added with 1 mg Co(NO3)2·6H2O, and after standing for 20 h, the Co(NO3)2·6H2O self-assembled based on electrostatic attraction was obtained. 0.0034 (Mo3S 11 ) 0.0064 Solution, 5mL of Co 0.0034 (Mo3S 11 ) 0.0064 The solution was dripped at a rate of 0.2 mL / min onto a nickel foam substrate (5 cm × 5 cm) that had been ultrasonically cleaned with 1 mol / L hydrochloric acid and anhydrous ethanol for 12 min, and self-assembled at 50 °C for 3 h to obtain a M with a nano-network structure. m (Mo3S 11 ) n / Ni Foam catalyst, named Co 0.0034 (Mo3S 11 ) 0.0064 / Nifoam catalyst.
[0052] This embodiment also provides a nano-network structure M m (Mo3S 11 ) n / Ni Foam catalyst is prepared by the above preparation method.
[0053] Example 4
[0054] This embodiment provides a nano-network structure. m (Mo3S 11 ) n The preparation method of the Ni Foam catalyst comprises the following steps:
[0055] 40g of sulfur powder was added to 120mL of ammonium sulfide solution to obtain a polysulfide ammonium solution with a concentration of 25%; 4g of ammonium molybdate was then added to 120mL of the polysulfide ammonium solution, and the mixture was reacted in an oil bath at 95°C for 5 days to obtain a crude product, which was then washed with 400mL of carbon disulfide and deionized water, centrifuged at 6000r / min, and dried at 60°C for 10h to obtain (NH4)2Mo3S 13 ·2H2O; 10mg(NH4)2Mo3S 13 2H2O was dissolved in 3mL DMF to obtain (NH4)2Mo3S 13 ·2H2O colloidal solution, to (NH4)2Mo3S 13 ·2H2O colloidal solution was added with 2 mg Fe(SO4)2·6H2O, and after standing for 24 h, Fe(SO4)2·6H2O was obtained based on electrostatic attraction self-assembly. 0.0056 (Mo3S 11 ) 0.0128 Solution, 7mL of Fe 0.0056 (Mo3S 11 ) 0.0128 The solution was dripped at a rate of 0.2 mL / min onto a nickel foam substrate (5 cm × 5 cm) that had been ultrasonically cleaned with 1 mol / L hydrochloric acid and anhydrous ethanol for 12 min, and self-assembled at 60 °C for 4 h to obtain a M with a nano-network structure. m (Mo3S 11 ) n / Ni Foam catalyst, named Fe 0.0056 (Mo3S 11 ) 0.0128 / Nifoam catalyst.
[0056] This embodiment also provides a nano-network structure M m (Mo3S 11 ) n / Ni Foam catalyst is prepared by the above preparation method.
[0057] Comparative Example
[0058] Comparative Example 1
[0059] The difference between Comparative Example 1 and Example 1 is that only nickel nitrate is loaded on the Ni foam substrate, as follows:
[0060] 2 mg of nickel nitrate was dissolved in 3 mL of DMF and allowed to stand for 24 h to obtain a nickel nitrate solution based on electrostatic attraction self-assembly. 7 mL of the nickel nitrate solution was dropped at a drop casting rate of 0.2 mL / min onto a nickel foam substrate (5 cm × 5 cm) that had been ultrasonically cleaned with 1 mol / L hydrochloric acid and anhydrous ethanol for 12 min. The nickel nitrate catalyst was self-assembled at 60 ° C for 4 h to obtain a nickel nitrate catalyst with a nano-network structure, named Ni 2+ -Ni foam.
[0061] Comparative Example 2
[0062] The difference between Comparative Example 2 and Example 1 is that only copper nitrate is loaded on the Ni foam substrate, as follows:
[0063] 1 mg of copper nitrate was dissolved in 3 mL of DMF and allowed to stand for 24 h to obtain a copper nitrate solution based on electrostatic attraction self-assembly. 3 mL of the copper nitrate solution was dropped at a rate of 0.2 mL / min onto a nickel foam substrate (5 cm × 5 cm) that had been ultrasonically cleaned with 1 mol / L hydrochloric acid and anhydrous ethanol for 12 min. The solution was self-assembled at 60 ° C for 4 h to obtain a copper nitrate catalyst with a nano-network structure, named Cu 2+ -Ni foam.
[0064] Comparative Example 3
[0065] The difference between Comparative Example 3 and Example 1 is that only cobalt nitrate is loaded on the Ni foam substrate, as follows:
[0066] 1 mg of cobalt nitrate was dissolved in 3 mL of DMF and allowed to stand for 24 h to obtain a cobalt nitrate solution based on electrostatic attraction self-assembly. 5 mL of the cobalt nitrate solution was dropped at a drop casting rate of 0.2 mL / min onto a nickel foam substrate (5 cm × 5 cm) that had been ultrasonically cleaned with 1 mol / L hydrochloric acid and anhydrous ethanol for 12 min. The solution was self-assembled at 60 ° C for 4 h to obtain a cobalt nitrate catalyst with a nano-network structure, named Co 2+ -Ni foam.
[0067] Comparative Example 4
[0068] The difference between Comparative Example 4 and Example 1 is that only ferrous nitrate is loaded on the Ni foam substrate, as follows:
[0069] 2 mg of ferrous nitrate was dissolved in 3 mL of DMF and allowed to stand for 24 h to obtain a ferrous nitrate solution based on electrostatic attraction self-assembly. 7 mL of ferrous nitrate solution was added at a drop casting rate of 0.2 mL / min onto a nickel foam substrate (5 cm × 5 cm) that had been ultrasonically cleaned with 1 mol / L hydrochloric acid and anhydrous ethanol for 12 min. The catalyst was self-assembled at 60 ° C for 4 h to obtain a ferrous nitrate catalyst with a nano-network structure, named Fe 2+ -Ni foam.
[0070] Comparative Example 5
[0071] The difference between Comparative Example 5 and Example 1 is that only [Mo3S 13 ] 2- Loaded on Ni foam substrate, as follows:
[0072] 10mg(NH4)2Mo3S 13 2H2O was dissolved in 3mL DMF and allowed to stand for 24h to obtain a solution based on electrostatic attraction self-assembly. 7mL of the solution was dropped at a rate of 0.2mL / min onto a nickel foam substrate (5cm×5cm) that had been ultrasonically cleaned with 1mol / L hydrochloric acid and anhydrous ethanol for 12min. The solution was self-assembled at 60℃ for 4h to obtain a catalyst with a nano-network structure, named [Mo3S 13 ] 2- -Ni foam.
[0073] Experimental example
[0074] Experimental Example 1
[0075] The Ni obtained in Example 1 was examined using a scanning electron microscope. 0.0068 (Mo3S 11 ) 0.0128 / Ni Foam catalyst morphology was observed, and the results are shown in Figure 1 .
[0076] Figure 1 The Ni obtained in Example 1 0.0068 (Mo3S 11 ) 0.0128 / Ni Foam catalyst SEM image. Figure 1 It can be seen that the Ni assembled on the nickel foam substrate 0.0068 (Mo3S 11 ) 0.0128 It has a nano-network structure.
[0077] Experimental Example 2
[0078] The Ni obtained in Example 1 was analyzed by X-ray diffraction. 0.0068 (Mo3S11 ) 0.0128 / Ni Foam catalyst crystal structure was observed, the results are shown in Figure 2 .
[0079] Figure 2 The Ni obtained in Example 1 0.0068 (Mo3S 11 ) 0.0128 XRD pattern of / Ni Foam catalyst. Figure 2 It can be seen that compared with Ni foam (nickel foam), Ni 0.0068 (Mo3S 11 ) 0.0128 The peak intensity of the nickel substrate is significantly weakened. The above results indicate that Ni 0.0068 (Mo3S 11 ) 0.0128 An amorphous state is formed.
[0080] Experimental Example 3
[0081] The Ni obtained in Example 1 0.0068 (Mo3S 11 ) 0.0128 The effect of / Ni Foam catalyst in the degradation of tetracycline hydrochloride in the persulfate advanced oxidation system was tested as follows:
[0082] The 7 mL Ni obtained in Example 1 0.0068 (Mo3S 11 ) 0.0128 / Ni Foam catalyst was added to 10mg / L tetracycline hydrochloride pollutant, and adsorbed for 30min in dark conditions to achieve adsorption-desorption equilibrium between the catalyst and the solution, and 0.01-0.03g PMS was added; photocatalysis and PMS activation reaction were started under simulated sunlight illumination; after regular sampling, the absorbance of the tetracycline hydrochloride was tested using a UV-Vis spectrophotometer to observe its concentration change; the control group was not loaded with Ni 0.0068 (Mo3S 11 ) 0.0128 Ni foam, the results are shown in Figure 3 .
[0083] Figure 3 M obtained in Example 1 m (Mo3S 11 ) n / Ni Foam catalyst in the persulfate advanced oxidation system to degrade tetracycline hydrochloride. Figure 3 It can be seen that compared with unloaded Ni 0.0068 (Mo3S 11 ) 0.0128Ni foam, Example 1 loaded with Ni 0.0068 (Mo3S 11 ) 0.0128 Ni foam obtained M m (Mo3S 11 ) n / Ni Foam catalyst has significantly improved the degradation effect of tetracycline hydrochloride.
[0084] Experimental Example 4
[0085] The M obtained in Example 1 under different lighting conditions m (Mo3S 11 ) n The effect of / Ni Foam catalyst in the degradation of tetracycline hydrochloride in the persulfate advanced oxidation system was tested as follows:
[0086] The Ni obtained in Example 1 0.0068 (Mo3S 11 ) 0.0128 / Ni Foam catalyst (5cm×5cm) was added to 100mL of tetracycline hydrochloride pollutant with a concentration of 10mg / L, and adsorbed for 30min under dark conditions to achieve adsorption-desorption equilibrium between the catalyst and the solution; 0.01-0.03g PMS was added; photocatalysis and PMS activation reaction were started under simulated sunlight illumination; after regular sampling, the absorbance of the tetracycline hydrochloride was tested using a UV-Vis spectrophotometer to observe its concentration change; at the same time, the MoS obtained in Example 1 was set to be only under dark conditions. x / Experimental results of nickel foam catalyst in persulfate advanced oxidation system for degradation of tetracycline hydrochloride Figure 4 .
[0087] Figure 4 Ni obtained in Example 1 under different illumination conditions 0.0068 (Mo3S 11 ) 0.0128 / Ni Foam catalyst in the persulfate advanced oxidation system to degrade tetracycline hydrochloride. Figure 4 It is known that, whether under light conditions or dark conditions, the Ni 0.0068 (Mo3S 11 ) 0.0128 / Ni Foam catalysts have excellent effects in degrading tetracycline hydrochloride.
[0088] Experimental Example 5
[0089] The effects of the catalysts obtained in Examples 1-4 and Comparative Examples 1-5 on the degradation of tetracycline hydrochloride in a persulfate advanced oxidation system are as follows:
[0090] Take 5 cm × 5 cm of the catalyst obtained in Examples 1-4 and Comparative Examples 1-5, respectively, and add them to 100 mL of tetracycline hydrochloride pollutant with a concentration of 10 mg / L. Adsorb for 30 min in dark conditions to achieve adsorption-desorption equilibrium between the catalyst and the solution, and add 0.01-0.03 g of PMS; start photocatalysis and PMS activation reaction under simulated sunlight illumination; after regular sampling, use a UV-Vis spectrophotometer to test the absorbance of the tetracycline hydrochloride taken, and observe the concentration change results. See Figure 5-6 .
[0091] Figure 5 M obtained in Example 1-4 m (Mo3S 11 ) n / Graphic showing the effect of Ni Foam catalyst in the persulfate advanced oxidation system in the degradation of tetracycline hydrochloride. Figure 6 This is a graph showing the effect of the materials obtained in Comparative Examples 1-5 on the degradation of tetracycline hydrochloride in a persulfate advanced oxidation system. Figure 5-6 It can be seen that compared with comparative examples 1-5 only loading metals or only loading molybdenum-sulfur clusters, the MoSx / nickel foam catalyst obtained in examples 1-4 has a significantly enhanced effect in degrading tetracycline hydrochloride in a persulfate advanced oxidation system.
[0092] In summary, the M obtained by the present invention m (Mo3S 11 ) n / Ni Foam catalyst has excellent ability to activate PMS to remove antibiotic pollutants.
[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. On the basis of the present invention, some modifications or replacements may be made thereto, but these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of protection claimed by the present invention.
Claims
1. A M with a nano-network structure m (Mo3S 11 ) n / Ni Foam catalyst preparation method, characterized in that, The following steps are involved: (1) To (NH4)2Mo3S 13 After adding metal salt M to the 2H2O colloidal solution, M is obtained through self-assembly m (Mo3S 11 ) n Solution; (2) Replace the M in step (1) m (Mo3S 11 ) n The solution is added to the cleaned nickel foam substrate and self-assembled to obtain the product.
2. The M having a nano-network structure according to claim 1 m (Mo3S 11 ) n / Ni Foam catalyst preparation method, characterized in that, The metal salt M, (NH4)2Mo3S 13 The mass ratio of 2H2O is 1:(3-10); the metal salt M is selected from one of nickel salt, cobalt salt, copper salt and ferrous salt; the self-assembly time is 12-24h.
3. The M having a nano-network structure according to claim 1 m (Mo3S 11 ) n / Ni Foam catalyst preparation method, characterized in that, (NH4)2Mo3S in step (1) 13 The concentration of 2H2O colloidal solution is 1-4 mg / mL.
4. The M having a nano-network structure according to claim 1 m (Mo3S 11 ) n / Ni Foam catalyst preparation method, characterized in that, In step (2), M m (Mo3S 11 ) n The dosage of the solution is 0.1-0.4mL / cm 2 ; The value range of m is 0.0028-0.0176, and the value range of n is 0.0064-0.0128.
5. The M having a nano-network structure according to claim 1 m (Mo3S 11 ) n / Ni Foam catalyst preparation method, characterized in that, The self-assembly temperature in step (2) is 40-60° C., and the self-assembly time is 3-5 hours.
6. The M having a nano-network structure according to claim 1 m (Mo3S 11 ) n / Ni Foam catalyst preparation method, characterized in that, (NH4)2Mo3S in step (1) 13 The preparation process of 2H2O is as follows: sulfur powder is added to ammonium sulfide solution to obtain polyammonium sulfide solution; ammonium molybdate is added to the polyammonium sulfide solution for reaction, and the obtained product is obtained after purification.
7. The M having a nano-network structure according to claim 6. m (Mo3S 11 ) n / Ni Foam catalyst preparation method, characterized in that, The usage ratio of the ammonium sulfide solution and the sulfur powder is (3-4) mL: 1 g; the usage ratio of the ammonium polysulfide solution and ammonium molybdate is (30-60) mL: 1 g; and the concentration of the ammonium polysulfide solution is 20-25%.
8. The M having a nano-network structure according to claim 6 m (Mo3S 11 ) n / Ni Foam catalyst preparation method, characterized in that, The reaction temperature is 90-95°C and the reaction time is 4-5 days.
9. A M with a nano-network structure m (Mo3S 11 ) n / Ni Foam catalyst, characterized in that The preparation method is described in any one of claims 1 to 8.
10. The M having a nano-network structure according to claim 9. m (Mo3S 11 ) n Application of / Ni Foam catalyst in activated PMS oxidative degradation of organic pollutants.
Citation Information
Patent Citations
Sea urchin-shaped MoS2 / foamed nickel composite capacitor electrode material and preparation method thereof
CN114843109A
Cited By
Ni-coated NiS2-coated MoSx / NF composite catalyst and preparation method and application thereof
CN120679565A